EpCAM and gpA33 are markers of Barrett's metaplasia. Issue 3 (10th February 2006) - Wong, N A C S; Warren, B F; Piris, J; Maynard, N; Marshall, R; Bodmer, W F
Abstract : Aims: To characterise a specific and sensitive marker of Barrett's metaplasia (BM). Methods: Cases of normal oesophageal squamous mucosa (11 fresh endoscopic biopsies and 10 formalin fixed, paraffin embedded tissue blocks), BM (11 biopsies and 11 tissue blocks), and normal gastric body mucosa (five biopsies and five tissue blocks) were analysed using reverse transcriptase PCR, Western blotting, and immunohistochemistry for EpCAM, and reverse transcriptase PCR for gpA33. Results: Strong EpCAM mRNA expression was detected in all the BM cases, in contrast to weak expression in all the normal gastric mucosal samples and no expression in any of the normal oesophageal mucosal samples tested. Strong gpA33 mRNA expression was detected in all the BM cases, in contrast to weak expression in a quarter of the normal gastric mucosal samples and no expression in any of the normal oesophageal mucosal samples tested. Western blotting showed EpCAM protein expression in all the BM cases and in none of the normal gastric or oesophageal mucosal samples tested. Immunohistochemistry showed strong EpCAM protein expression in BM and complete absence of expression in normal oesophageal squamous epithelium. Scattered EpCAM expressing cells were found in the gland bases of normal gastric body mucosa. Conclusions: EpCAM protein and gpA33 mRNA expressions are specific and sensitive markers of BM.